MURID TPA/TPSA/MDA DALAM PERSPEKTIF PSIKOLOGI PERKEMBANGAN ANAK - Wahidah Fitriani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
TPA/TPSA/MDA are informal Islamic educational institutions. These institutions are expected to give hopes for Moslems for quality improvement of their children. However, such institutions are not yet professionally managed. Fund constrains, less professional management, less systematic curriculums and less qualified teachers are the major common problems faced by the institutions. Consequently, the quality of learning process cannot be well assured. As one of the most influential components of learning, the teachers are not well selected and prepared. Most teachers are volunteers. They are not well prepared, especially in the area of child developmental psychology. This paper elaborates the importance of child developmental psychology to be possessed by teachers who are prepared to be more qualified in teaching at TPA/TPSA/MDA.Kata Kunci: TPA/TPSA/MDA, psikologi perkembangan, perkembangan anak